"I Have Lost Me": Zhuangzi's Butterfly Dream. Issue 3 (September 2013) - Yao, Zhihua
Abstract The parable of the butterfly dream is one of the most interesting and influential passages among Zhuangzi's beautiful writings. This article interprets the butterfly dream from an interdisciplinary approach. The review of mythological and religious sources reveals that the image of the butterfly is widely understood to symbolize the human self or soul. The scientific study of dream experience touches upon the issue of self‐consciousness and the sense of two‐tiered self. The philosophical and psychological perspectives further highlight the tension between the wu 吾‐self and the wo 我‐self, self and ego, bodily and spiritual soul, and allow me to test my hypothesis of self‐alienation.